Statistical analysis of design codes calculation methods for punching sheer resistance in column‐to‐slab connections - Zabulionis, Darius; Šakinis, Dainius; Vainiūnas, Povilas (Journal of Civil Engineering and Management, 2006)
This paper analyses the compliance of the design codes calculation methods for punching shear resistance in reinforced concrete slabs STR 2.05.05:2005, E DIN 1045–1, ENV 1992–1‐1 EC 2, prEN 1992–1 [Final draft] EC 2, Model Code CEB‐FIP 1990, BS 8110, ACI 318–99 to the experimental data. It has been analysed whether the difference in the results of the mean punching shear resistance received according to these methods and through experiments is statistically significant, when the level of significance value is 0,05. To analyse the significance of the difference of the means Student t test was used. An analysis was carried out to find out which methods show the least different resistance results from the experimental data. According to this analysis, a classification of methods was made. Student t test was applied to analyse in which methods the ratio between the punching shear resistance results obtained and the punching shear resistance results received through experiment is statistically insignificant. The level of significance value considered was 0,05. It has been determined that almost in all cases the difference between the punching shear resistance results received experimentally and theoretically is statistically significant. It has also been found out that generally the punching shear resistance can be calculated by applying the prEN 1992–1 [Final draft] EC 2 method. The best method to describe the punching shear resistance in minimally reinforced slabs is ACI 318. The worst results are obtained by applying ENV 1992–1‐1 EC 2 and E DIN 1045–1 methods.Kolonos-plokštės jungties be skersinio armavimo veikiant sutelktajai apkrovai praspaudžiamojo stiprio normatyvinių skaičiavimo metodikų statistinė analizėSantrauka. Darbe nagrinėjamas gelžbetoninių plokščių praspaudžiamojo stiprio skaičiavimo normatyvinių metodikų STR 2.05.05:2005, E DIN 1045-1, ENV 1992-1-1 EC 2, prEN 1992-1 [Final draft] EC 2, Model Code CEB-FIP 1990, BS 8110, AC 318 atitikimas eksperimentiniams duomenims. Išanalizuota, ar pagal šias metodikas apskaičiuotų ir eksperimentiškai nustatytų praspaudžiamojo vidutinių stiprio reikšmių skirtumas statistiškai reikšmingas, kai reikšmingumo lygmuo yra 0,05. Vidurkių skirtumo reikšmingumo analizei naudotas Stjudento t kriterijus. Išnagrinėta, pagal kurias metodikas apskaičiuotos stiprio reikšmės mažiausiai skiriasi nuo eksperimentinių duomenų. Tuo remiantis metodikoms priskirti rangai. Taikant Stjudento t kriterijų, išanalizuota, pagal kurias metodikas apskaičiuotų praspaudžiamojo stiprio reikšmių santykis su eksperimentiškai nustatytomis praspaudžiamojo stiprio reikšmėmis statistiškai nereikšmingas. Reikšmingumo lygmuo imtas 0,05. Nustatyta, kad beveik visais atvejais skirtumas tarp eksperimentiškai ir teoriškai apskaičiuotų praspaudžiamojo stiprio reikšmių statistiškai reikšmingas. Taip pat nustatyta, kad tiksliausiai praspaudžiamąjį stiprį galima apskaičiuoti pagal prEN 1992-1 [Final draft] EC 2 metodiką.Raktiniai žodžiai: gelžbetoninių plokščių praspaudžiamasis stipris, gelžbetoninių plokščių projektavimo normos, praspaudžiamojo stiprio statistinė analizė.First Published Online: 14 Oct 2010